Social Embeddedness and Economic Behaviour in Pesantren Mlangi - Mustaghfiroh Rahayu (Shirkah: Journal of Economics and Business, 2019)
In contrast to global research on the relationship between Islam and entrepreneurship, analyses which shows a negative trend, researches on this topic in Indonesia show different findings. Various researches show the positive impact of the teachings of Islam on Muslim entrepreneurial behaviour, including multiple studies conducted in Mlangi. Continuing the existing research, this research looks at the role of pesantren networks in entrepreneurial practices carried out by entrepreneurs as well as caregivers for pesantren in Mlangi. By using the social embeddedness theory, this research found out that there is a dialogue between rational choice, social context and pesantren networks in the business run by entrepreneurs cum caregivers of pesantren in Mlangi.Â Keywords: social embededdness), Mlangi, pesantren entrepreneur